Optimal Ordering and Disposing Policies in the Presence of an Overconfident Retailer: A Stackelberg Game. (22nd January 2015) - Wang, Zhigang; Zhang, Zhenchao; Li, Chunfa; Xu, Lei; You, Chang
Abstract : This paper investigates the impact of the retailer's overconfident behavior on supply chain performance. We start with a basic model on the rational newsvendor model and investigate the retailer's optimal ordering decision and expected profit. Next, we extend the basic model and introduce an overconfident retailer. We find that the retailer's overconfident behavior does not necessarily damage the supply chain compared with the basic model when the overconfident level does not exceed a threshold. We also design the cooperation and buyback mechanism and conduct numerical analysis to compare the manufacturer's and retailer's expected profits and real profits with those in the basic newsvendor model. It can achieve Pareto improvement in the supply chain when the overconfident level is low. When the retailer's overconfident level exceeds a threshold, the retailer's ordering decision cannot make the whole supply chain sustainable development.